Capital Flow Regulations: The Effects of Liquidity and Dividend on the Financial Reporting Quality Evidence from Middle Eastern countries - Fakhreddin Mirsamee, Seyed; A. Ahanchi , Mahsa (International Journal of Business Management and Entrepreneurship, 2022)
Dividend policy has been an influential factor in corporate investment decisions and has been an issue in recent years. The monetary policy began with the creation of economic organizations and free trade markets during the financial crisis. These were the first examples of capital controls in the history of the European Union and had different effects on the financial position of companies. Since the Central Bank, the monetary policy council or any other monetary committee will change the volume of money by declaring and implementing monetary policies, we try to use a sample of the Middle East countries to distinguish between economic austerity and capital control and to assess the effects of the dividend on corporate capital decisions. All sample countries have a common financial reporting framework (International Financial Reporting Standards - IFRS), and some have a range of measures, from low-tight measures such as tax increases to more stringent measures such as enforcing capital controls. They implemented in order to stabilize their economy. To do this, we will specifically use two factors that determine information asymmetry in accounting: conditional conservatism and the level of revenue management.